Therapeutic properties of the Atlas pistachio tree (Pistacia atlantica Desf.) in the Naâma region (Algeria) - Belaid, Souaad; Nouri, Tayeb; Benaradj, Abdelkrim (Biodiversity: Research and Conservation, 2024)
The Atlas pistachio tree (Pistacia atlantica) is a woody deciduous species from the family Anacardiaceae. It thrives in the steppe plains and Saharan Atlas of the Naâma region in south-western Algeria. This tree is well known in traditional Algerian medicine for its active phenolic compounds, particularly those found in its seeds and leaves. To promote its use, an ethnobotanical survey was conducted among herbalists and other knowledgeable individuals in the Naâma region, utilizing 100 questionnaires divided among 25 municipalities. The findings revealed that leaves (42%) and fruits (31%) are the most commonly utilized parts. The predominant preparation methods include decoction and grinding, but also other forms are popular, such as herbal tea or powder mixed with honey, dates, milk, or water. Administration is mainly oral, though external applications are also common, particularly for localized issues. The most frequently treated conditions include oral diseases, stomach ulcers, respiratory infections, Malta fever, and skin rashes, with values of fidelity index ranging from 2% to 14%. Most reported outcomes from these treatments are positive, indicating either cures or improvements. The frequency of use for this plant among the respondents is 100%, underscoring its significant cultural importance. The informant consensus exceeded 0.70, reflecting a robust therapeutic understanding of the plant. The global knowledge index regarding its uses is notably high, highlighting its essential role in the community for medicinal and other applications.